The Effect of Realistic Mathematics Education Approach on Students' Conceptual Understanding - Ahmad Nizar Rangkuti; Mariam Nasution; Almira Amir; Irwan Saleh Dalimunthe; Samsuddin Samsuddin; Muhammad Amin; Dame Siregar; Mhd. Rafi'i Ma'arif Tarigan (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This research was conducted in Grade VI at SD 200223 Sibulan-bulan Padangsidimpuan during the academic year 2023/2024, focusing on the topic of fractions. The aim of this study was to determine the effect of the Realistic Mathematics Approach on students' understanding of concepts in Grade VI at SD 200223 Sibulan-bulan. The study utilized a Post-Test-Only Control Group design and was of quasi-experimental nature. It involved an experimental group receiving the Realistic Mathematics Education Approach treatment and a control group not receiving such treatment. Both groups were selected randomly. The research findings indicate that students' understanding of mathematical concepts was better when using the Realistic Mathematics Approach compared to conventional learning methods. Based on the hypothesis testing results, it was found that t-count > t-table (2.23 > 1.98) and the Sig. value = 0.018, indicating that there is a positive effect of the Realistic Mathematics Education Approach (RME) on students' conceptual understanding. Based on the above findings, it is recommended that the learning process in schools use the Realistic Mathematics Education Approach, as it can improve students' conceptual understanding and mathematical abilities.